A Model of the Ectomycorrhizal Contribution to Forest Soil C and N Dynamics and Tree N Supply Within the EFIMOD3 Model System - Oleg Chertov; Pavel Frolov; Vladimir Shanin; Irina Priputina; Sergey Bykhovets; Anna Geraskina (Plants)
Mycorrhizal symbiosis has been the focus of research for more than a century due to the positive effect of fungi on the growth of the majority of woody plants. The extramatrical mycelium (EMM) of ectomycorrhiza (EMR) accounts for up to one-third of the total soil microbial biomass, whereas litter from this short-living pool accounts for 60% of the total litterfall mass in forest ecosystems. The functioning of EMR improves the nitrogen (N) nutrition of trees and thus contributes to the carbon (C) balance of forest soils. The model presented here is an attempt to describe these EMR functions quantitatively. It calculates the growth of EMM and the subsequent “mining” of additional nitrogen from recalcitrant soil organic matter (SOM) for EMR growth, with the associated formation of “dissolved soil carbon”. The decomposition of EMM litter is carried out by all organisms in the soil food webs, forming available <semantics><msubsup>NH4+</msubsup></semantics> in the first phase and then solid-phase by-products (excretes) as a new labile SOM pool. These substances are the feedback that determines the positive role of EMR symbiosis for forest vegetation. A sensitivity analysis revealed a leading role of the C:N ratio of biotic components in the dynamics of EMM. The model validation showed a satisfactory agreement between simulated and observed data in relation to EMM respiration in larch forest plantations of different ages. Model testing within the EFIMOD3 model system allowed a quantitative assessment of the contribution of different components to forest soil and ecosystem respiration. The validation and testing of this model demonstrated the adequacy of the theoretical background used in this model, with a fast EMM decomposition cycle by all soil biota of the food webs and without direct resource exchange between plants and fungi.